Growth Mindset In Teaching 3D Animation Shapes For Beginner - Novi, Fitrianingaih; Makawi, Faizal; Aswar; Hatta, Harmin (Journal of Arts Education and Design, 2024)
This research aims to equip the Stofo community with the necessary skills and knowledge to effectively use the 3D Max application for comic creation. The goal is to empower participants with not only the technical skills but also the mindset needed to utilize this 3D modelling software effectively. This is crucial because 3D modelling plays a pivotal role in the global comic creation industry. By mastering 3D modelling, Stofo comic artists can produce comic chapters and explore various aspects of industrial design and web tone in the context of the Fourth Industrial Revolution and Society 5.0. The method of this research is a qualitative approach involves instilling an understanding of the significance of learning 3D modelling and offering step-by-step tutorials within a computer lab. All participants will receive gradual instruction, starting with the basics of the 3D Max application, including commonly used tools and the creation of simple 3D models. The outcomes of this endeavour demonstrate that: (1) participants exhibit a strong interest in using 3D modelling for comic creation after receiving growth mindset theory; (2) they can produce fundamental 3D models for comic backgrounds with five (5) at high level, six 6 at intermediate level, and nine (9) at beginner level; and (3) they are enthusiastic about honing their 3D modelling skills for comic purposes. Therefore, It is crucial to empowers the Stofo community with 3D modelling skills and mindset, fostering creativity and potential in the realm of comics and design.